Penerapan Media Pembelajaran Berbasis Genially untuk Meningkatkan Hasil Belajar Geografi Bagi Siswa Kelas XI di SMA Swasta Cendana Mandau - Fadhil, Alifiah Azizah Al; Novio, Rery (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to determine whether the application of Genially as a learning medium can improve Geography learning outcomes at Cendana Mandau Private High School. The method used is a pre-experimental method with a one-group pretest-posttest design. The subjects in this study were 21 students in Class IX, Package 5. Data collection techniques included pre-test and post-test questions, as well as student response questionnaires. Test results were analyzed using SPSS for IKBM and student responses using descriptive analysis. Data analysis involved normality tests, homogeneity tests, and hypothesis testing. The research results indicate that the t-test significance value (2-tailed) for the pretest and posttest is 0.000 < 0.05, meaning Ha is accepted, indicating an improvement in learning outcomes with the application of the Genially medium. Therefore, it can be concluded that using Genially-based media can enhance the learning outcomes of students in Class XI, Package 5, at Cendana Mandau Private High School.